O estado da arte de pesquisas acadêmicas sobre a Olimpíada Brasileira de Matemática da Escolas Públicas - Evangelista, Aline Susan (Universidade Federal de São Carlos, 2021)
This study aimed to analyze the teaching-learning process of school contents in research on the Brazilian Public Schools Mathematics Olympiad (OBMEP). For the methodological path we use the State of Art as a modality of a qualitative research. From the thesis database of the Coordination for the Improvement of Higher Education Personnel - CAPES and the Digital Library of Theses and Dissertations - BDTD, 25 Master's dissertations involving the research object were catalogued, defended in the period from 2009 to 2020. We adopted as an analysis criterion for these academic productions the thematic unit in question: 1 work in Algebra, 1 in Function, 1 with Numerical Sequences, 1 involving Statistics, 5 discussing Problem Solving and 16 papers with Geometry. As results of our research we highlight that dissertations bring different teaching proposals using OBMEP questions. Each one of the dissertations had a different approach since, on the one hand, there were dissertations that addressed in detail what would be worked and brought a broad theoretical contribution and, on the other hand, there were also works that did not present their objectives, the methodology used or the theoretical foundation. In addition, it was possible, throughout the research, to verify that many authors chose to use GeoGebra software as an auxiliary tool in teaching. Some of the papers focused on the resolution of OBMEP questions in an algebraic way and there were dissertations in which the authors chose to analyze the students' errors.
The state of the art of academic research on the Brazilian Public Schools' Mathematics Olympiad
Keywords: Resolução de problemas; Educação básica; Mapeamento de pesquisas; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM